Absolute Polar Duty Cycle Division Multiplexing for High-Speed Fiber Optic Communication System - Malekmohammadi, Amin (2009)
Multiplexing is one of the fundamental necessities in today’s digital communications. It allows multiple users to share the bandwidth of the transmission medium. In this dissertation a new design of the Duty cycle Division Multiplexing (DCDM) family, namely Absolute Polar Duty Cycle Division Multiplexing (APDCDM) which is based on the polar signaling and different return to zero (RZ) duty cycles is reported for high speed optical fiber communication systems. Unlike all the other techniques, in AP-DCDM different users share the communication medium to transmit in the same time period and at the same carrier wavelength, but with different duty cycles. The unique duty cycle for each channel helps to regenerate data at the receiver. Two different AP-DCDM designs, namely AP-DCDM with guard band (GB) and AP-DCDM without GB have been successfully demonstrated. This thesis is presented based on the alternative format which has been approved by University Putra Malaysia’s Senate, which is the manuscript-based format. The major difference between this alternative format and the conventional ones is that, this format uses published papers in place of the regular chapters on results and discussion. The first paper contains a novel concept of decision circuit and Bit-error-rate (BER) estimation method for AP-DCDM which is published in International Review of Electrical Engineering. This journal in indexed by ISI Thomson Scientific. The concepts have significant differences to those used in conventional microwave communication receivers. This is due to the unique characteristics of the multilevel signal produced in AP-DCDM system. The BER estimation method is validated by simulation and compared against bit-to-bit comparison method. The second paper contains the first design of AP-DCDM (AP-DCDM with guard band) which is published in Optical Fiber Technology journal (OFT) by Elsevier. This journal is indexed by ISI Thomson Scientific with 2008 impact factor of 1.253. It is demonstrated that AP-DCDM system has a clear advantage over conventional RZOOK. Complexity and performance comparison against other modulation formats namely Duobinary, Non-Return-to-Zero (NRZ)-OOK and RZ-Differential Quadrature Phase-Shift Keying (RZ-DQPSK) at aggregate speed of 40 Gb/s (2 x 20 Gb/s) are made. It is shown that AP-DCDM has less complexity and the best receiver sensitivity (-32 dBm) and better CD tolerance (±200 ps/nm). In reference to duobinary, AP-DCDM is less complex and has better receiver sensitivity but worse dispersion tolerance The third paper contains the second design of AP-DCDM (AP-DCDM without guard band) which is published in IET Journal of Optoelectronics by Institution of Engineering and Technology (IET), previously IEE. This journal is indexed by ISI Thomson Scientific with impact factor of 0.704. The system tolerance to signal impairments is investigated and it shows that the spectral width of the AP-DCDM can be furthered reduced which leads to better dispersion tolerance compared to other modulation techniques. The fourth paper presents the effect of self-phase-modulation on AP-DCDM system which is accepted for publication in IET Journal of Optoelectronics (with impact factor of 0.704) considering different number of channels, launched power and precompensation ratio. It was shown that SPM is a major factor that introduce penalty to the system. Nonetheless, our results indicate that transmission using AP-DCDM should be possible at the launched power of up to tens of dBm, which is consistent with the requirement of high-quality, long distance transmissions. Finally the fifth paper discusses the performance evaluation of AP-DCDM over Wave length Division Multiplexing (WDM), which is accepted for publication in Optics Communications by Elsevier, which is indexed by ISI Thomson Scientific with 2008 impact factor of 1.552. The narrow optical spectrum on AP-DCDM reduces the inter-channel coherent crosstalk. The possibility of setting channel spacing as narrow as 62.5 GHz for 40 Gbit/s AP-DCDM signal was confirmed. A capacity of 1.28 Tbit/s (32 x 40 Gbit/s) was packed into a 15.5 nm EDFA gain-band with 0.64 bit/s/Hz spectral efficiency by using 10 Gbit/s transmitter and receiver.